2007
DOI: 10.1002/pi.2353
|View full text |Cite
|
Sign up to set email alerts
|

Interfacial polymerization of morphologically modified polyaniline: from hollow microspheres to nanowires

Abstract: BACKGROUND: Polyaniline (PANI) has attracted much attention in many fields due to its chemical and physical properties, and different nanostructures of PANI changing from one-dimensional to three-dimensional have been obtained. By changing the concentration of cetyltrimethylammonium bromide (CTAB), the morphology of hydrochloric acid-doped polyaniline could be changed from one-dimensional nanoneedles or nanowires with a network structure (50-100 nm in diameter) to three-dimensional hollow microspheres (ca 400 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(41 citation statements)
references
References 45 publications
1
39
0
Order By: Relevance
“…In the recent years, several techniques for synthesizing PANI nanostructures have been developed including template synthesis, 26 template-free synthesis, 27 seeding polymerization, 28,29 interfacial polymerization, [30][31][32] rapid mixing polymerization, 33 electrospinning, 34 and electrochemical polymerization. 35,36 Template method introduces ''structural directors'' in the polymerization bath that dictates the PANI nanostructures morphology.…”
Section: Introductionmentioning
confidence: 99%
“…In the recent years, several techniques for synthesizing PANI nanostructures have been developed including template synthesis, 26 template-free synthesis, 27 seeding polymerization, 28,29 interfacial polymerization, [30][31][32] rapid mixing polymerization, 33 electrospinning, 34 and electrochemical polymerization. 35,36 Template method introduces ''structural directors'' in the polymerization bath that dictates the PANI nanostructures morphology.…”
Section: Introductionmentioning
confidence: 99%
“…lower 2θ range from 5 to 35°. Pure polymer shows a comparatively crystalline behaviour with an intense peak at around 7⋅8° that is because of polymeric self-assembly (Li et al 2008). The crystallite size of Au particle can be calculated by line broadening for the highest intense peak using Scherer's equation…”
Section: Resultsmentioning
confidence: 99%
“…In some cases, the geometry is attributed to the coexistence of immiscible phases (oil/water), which allows the controlled generation of fibers [49,50]; however, other reports have demonstrated that fibers can be obtained in the aqueous phase [51]. The presence of surfactants (ionic or nonionic), which form micellar soft-templates is another mechanism which has also been used to explain fibrous geometries [52][53][54]. The synthesis of the MCM-41 structure is a clear example of this quality of surfactants.…”
Section: Morphologymentioning
confidence: 97%